Addressing county lines: praxis for community safety practitioners. Issue 2 (8th April 2019) - Andell, Paul
Abstract : Purpose: County lines involving the exploitation of vulnerable children and young people by gangs have been described as a bigger threat than the exploitation exposed by the Rotherham scandal ( The Times, 27 November 2017). The purpose of this paper is to explain the contingencies and drivers informing gang identities in the irregular economy of drugs and make some suggestions to address these. Design/methodology/approach: The paper discusses the social reality (ontology) of UK gangs in the UK and the different theories of knowledge about gangs (epistemologies) that can both help and hamper gangs' policy and practices. The paper is based on recent research and sets out strategic ideas for good community safety practice in order to develop multi-modal partnership interventions in gang-affected neighbourhoods. Recent policies are located within the broader political economy of crime, which raises questions of current policy direction to achieve safer neighbourhoods. Findings: A critical realist approach to gangs (Pitts, 2016 ) assumes that unobservable structures (patterns of relations and roles) cause observable events (gang behaviour). This suggests a reality of gangs independent of theories about them. In this paradigm, the author's theories about the world are historically, socially and culturally situated and always partial. Not only do gangs change in space and time, but also so do the author's representations of them. Research limitations/implications: Arguably, at this moment, the authors' best ideas about the underlying causal forces which precipitate gangs involve social structures which have push and pull factors acting in conjunction with culturally enmeshed individuals with limited choices. The pushes of social exclusionary factors such as institutional racism and unemployment act in consort with pull factors of excessive consumerism. However, the author's ideas about gangs are partial and fallible, and this demands a methodological pluralism that involves a range of stakeholders when researching and formulating appropriate interventions. Practical implications: To address the impact of gang violence at the micro or neighbourhood level, Andell and Pitts (2009, 2013, 2017) developed an interactive model of action research which is inclusive of the experiences and knowledge of stakeholders. This knowledge can be valuable not only to build multi-modal strategies in gang-affected neighbourhoods, but can also be useful as a reflexive spur to provide feedback and direction on what works to reduce community harms. Earlier research experience (Andell and Pitts 2009, 2013, 2017 ) informs ideas that that single agency or "siloed" approaches to problems associated with gangs and drug markets can cause confusion and mistrust for other stakeholders and that more integrated approaches are needed. Social implications: In order to assist young people to attain their potential with the assistance of institutions, both micro and macro changes need to take place. The social capital of community networks needs to be enhanced and the redistributive potential of economic policy needs to be enacted. Therefore, policy is needed which is founded on the belief that research is capable of understanding the mechanisms that produce material and cultural domination, and this analysis, in conjunction with stakeholder knowledge, could lead to a realistic program for collective actions in both the micro and macro spheres that reduce relative deprivation and curb the cultural mores for excess. Originality/value: The paper suggests a critical realist approach to gangs (Pitts, 2016 ) and assumes that unobservable structures (patterns of relations and roles) cause observable events (gang behaviour). This imputes a reality of gangs independent of theories about them. In this paradigm, the author's theories about the world are historical, socially and culturally situated and always partial. Not only do gangs change in space and time, but also so do the author's representations of them.